Anti-MAdCAM antibody (PF-00547659) for ulcerative colitis (TURANDOT): a phase 2, randomised, double-blind, placebo-controlled trial. Issue 10090 (8th July 2017) - Vermeire, Séverine; Sandborn, William J; Danese, Silvio; Hébuterne, Xavier; Salzberg, Bruce A; Klopocka, Maria; Tarabar, Dino; Vanasek, Tomas; Greguš, Miloš; Hellstern, Paul A; Kim, Joo Sung; Sparrow, Miles P; et al.
Summary: Background: PF-00547659 is a fully human monoclonal antibody that binds to human mucosal addressin cell adhesion molecule-1 (MAdCAM-1) to selectively reduce lymphocyte homing to the intestinal tract. We aimed to assess the efficacy and safety of PF-00547659 in patients with moderate to severe ulcerative colitis. Methods: This phase 2, randomised, double-blind, placebo-controlled clinical trial recruited patients aged 18–65 years from 105 centres in 21 countries, with a history (≥3 months) of active ulcerative colitis extending more than 15 cm beyond the anal verge (with a total Mayo score ≥6 and a Mayo endoscopic subscore ≥2) who had failed or were intolerant to at least one conventional therapy. Patients were stratified by previous anti-TNFα treatment, and randomly assigned by a computer-generated randomisation schedule to receive a subcutaneous injection of 7·5 mg, 22·5 mg, 75 mg, or 225 mg PF-00547659 or placebo at baseline, then every 4 weeks. Patients, investigators, and sponsors were blinded to the treatment. The primary endpoint was the proportion of patients achieving remission (total Mayo score ≤2 with no individual subscore >1 and rectal bleeding subscore ≤1) at week 12. The efficacy analysis included all patients who received at least one dose of the randomised treatment; the safety analysis was done according to treatment received. All p values were one-sided and multiplicity-adjusted. This study is registered with ClinicalTrials.gov, number NCT01620255 . Findings: Between Nov 2, 2012, and Feb 4, 2016, we screened 587 patients; 357 were eligible and randomly assigned to receive placebo (n=73) or PF-00547659 at doses of 7·5 mg (n=71), 22·5 mg (n=72), 75 mg (n=71), or 225 mg (n=70). Remission rates at week 12 were significantly greater in three of four active-treatment groups than in the placebo group (2·7% [two of 73]): 7·5 mg (11·3% [eight of 71]), 22·5 mg (16·7% [12 of 72]), 75 mg (15·5% [11 of 71]), and 225 mg (5·7% [four of 70]). These rates corresponded to a stratum-adjusted (anti-TNFα-naive and anti-TNFα-experienced) risk difference versus placebo of 8·0% for 7·5 mg (90% CI 1·9 to 14, p=0·0425), 12·8% for 22·5 mg (5·6 to 19·9, p=0·0099), 11·8% for 75 mg (4·8 to 18·8, p=0·0119), and 2·6% for 225 mg (−1·2 to 6·4, p=0·1803). Four of 73 (5·5%) patients had a serious adverse event in the placebo group, 11 of 71 (15·5%) in the 7·5 mg group, one of 70 (1·4%) in the 22·5 mg group, three of 73 (4·1%) in the 75 mg group, and three of 70 (4·3%) in the 225 mg group. No safety signal was observed for the study drug. Interpretation: PF-00547659 was safe and well tolerated in this patient population, and better than placebo for induction of remission in patients with moderate to severe ulcerative colitis. The greatest clinical effects were observed with the 22·5 mg and 75 mg doses. Funding: Pfizer.